Optical Methods and Instrumentation in Brain Imaging and Therapy - Madsen, Steen J. (Bioanalysis, Advanced Materials, Methods, and Devices, 2013)
This book provides a comprehensive up-to-date review of optical approaches used in brain imaging and therapy. It covers a variety of imaging techniques including diffuse optical imaging, laser speckle imaging, photoacoustic imaging and optical coherence tomography. A number of laser-based therapeutic approaches are reviewed, including photodynamic therapy, fluorescence guided resection and photothermal therapy. Fundamental principles and instrumentation are discussed for each imaging and therapeutic technique. Represents the first publication dedicated solely to optical diagnostics and therapeutics in the brain Provides a comprehensive review of the principles of each imaging/therapeutic modality Reviews the latest advances in instrumentation for optical diagnostics in the brain Discusses new optical-based therapeutic approaches for brain diseases.